Design and synthesis of potent PAR-1 antagonists based on vorapaxar. Issue 8 (15th April 2020) - Fan, Mengna; Han, Min; Xia, Yan; Zhang, Yingbin; Chu, Yang; Bai, Guirong; Li, Wei; Li, Ju; Zhao, Lihui; He, Yi; Ma, Xiaohui; Duan, Zhongyu
Graphical abstract: Abstract: A series of novel vorapaxar analogues with different amino substitutes at the C-7, C-9a and aromatic substitutes at the C-4 position were designed, synthesized, and evaluated for their inhibitory activity to PAR-1. Several compounds showed good potency in antagonist activity based on the intracellular calcium mobilization assay and excellent pharmacokinetics profile in rats. Among these analogues, 3d exhibited excellent PAR-1 inhibitory activity (IC50  = 0.18 μM) and the lower ability to cross the blood-brain barrier compared with vorapaxar (IC50  = 0.25 μM). Compound 3d has the potential to be developed as a new generation of PAR-1 antagonists with a better therapeutic window.